2021
DOI: 10.3389/fpls.2021.669053
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Biofortification of Crops–Challenges and Projected Benefits

Abstract: Despite Calcium (Ca) being an essential nutrient for humans, deficiency of Ca is becoming an ensuing public health problem worldwide. Breeding staple crops with higher Ca concentrations is a sustainable long-term strategy for alleviating Ca deficiency, and particular criteria for a successful breeding initiative need to be in place. This paper discusses current challenges and projected benefits of Ca-biofortified crops. The most important features of Ca nutrition in plants are presented along with explicit rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 148 publications
(208 reference statements)
0
14
0
Order By: Relevance
“…Super Basmati could be interesting in terms of human Ca nutrition. Similar to micronutrient deficiencies, also human Ca deficiency is a growing nutritional problem in human populations and suggested that the biofortification of stable food crops with Ca through plant breeding would be a sustainable solution to address human Ca deficiency [81].…”
Section: Discussionmentioning
confidence: 99%
“…Super Basmati could be interesting in terms of human Ca nutrition. Similar to micronutrient deficiencies, also human Ca deficiency is a growing nutritional problem in human populations and suggested that the biofortification of stable food crops with Ca through plant breeding would be a sustainable solution to address human Ca deficiency [81].…”
Section: Discussionmentioning
confidence: 99%
“…A number of edible plants are also naturally high in calcium, although the quantity and bioavailability are lower than animal‐source foods, especially dairy. The role of calcium and its distribution in plants has been extensively discussed elsewhere 27–30 . Briefly, plant roots are involved in tightly regulating the amount of calcium that the plant takes up via Ca 2+ ‐permeable cation channels.…”
Section: Promoting the Consumption Of Naturally Calcium‐rich Foodsmentioning
confidence: 99%
“…Inadequate consumption of any of these will result in adverse metabolic disturbances, leading to sickness, poor health, impaired development in children, and a large economic cost to society (1). Men and women aged between 25 and 50 years require a daily intake of 800 mg of calcium (Ca) and phosphorus (P), 280-350 mg of magnesium (Mg), 2,000 mg of potassium (K), 10-15 mg of Fe and Zn, 2-5 µg of manganese (Mn), and 500 mg of sodium (Na) to meet the Recommended Dietary Allowance (RDA) (10)(11)(12). This is reason enough for developing public health policies that encourage the consumption of micronutrients at the RDA levels.…”
Section: Introductionmentioning
confidence: 99%